The Yogyakarta Principles : principles on the application of international human rights law in relation to sexual orientation and gender identity ([s.n.] [S.l.], 2007)
Addresses a broad range of human rights standards and their application to issues of sexual orientation and gender identity. Affirms the primary obligation of states to implement human rights.
Keywords: HUMAN RIGHTS